The Effectiveness of the Integrated Project-Based Learning Model STEM to improve the Critical Thinking Skills of Elementary School Students - Akhmad, Yanuar; Masrukhi, Masrukhi; Indiatmoko, Bambang (Educational Management, 2020)
The purpose of this study was to analyze the effectiveness of the STEM-integrated PBP model to improve the creative thinking abilities of elementary school students. This type of research is a quantitative research method with a control group pre-test post-test design. The study population consisted of all grade IV students in Tersono District, Batang Regency. Samples were selected through a purposive sampling technique, so that selected class IV SD Negeri Rejosari 01, amounting to 20 students as an experimental group and SD Negeri Tersono, totaling 23 students as a control group. Data collection techniques used to test techniques, the results showed that the experimental class's creative thinking skills reached 85% classically with an average value of 80.75; while the creative thinking ability of control class classically only reaches 56.52% with an average value of 76.74. The N-gain score of the experimental class reached 0.51 with the medium category while the N-gain score of the control class only reached 0.33 with the low category.